PENGARUH SENYAWA SILAN TERHADAP SIFAT MEKANIK MATERIAL PELAPIS PADUAN HIBRID EPOKSI TERMODIFIKASI POLIURETAN - Savitri Savitri; Evi Triwulandari; Agus Haryono; O A Syahputra (Jurnal Kimia Terapan Indonesia, 2015)
Preparation of hybrid coating material from modified epoxy polyurethane (ETP) and silan (Si) has been done. Epoxy and polyurethane were modified with silan using γ-Glisidoksil propil trimetoksisilan (GPTMS) and γ-aminopropyl triethoxysilane (γ-APS) and also dibutyltindilaurate (DBTL) as catalyst. Fourier Transform Infrared (FTIR) characterization indicated that the hybrid coating material has been formed. The results of the analysis of NCO percent and conversion rate of isocyanates (α) also verified that the ETP-Si hybrid coatings have been formed. The addition 30% of silane as Si-O group indicated the rest of NCO percent was the lowest for hybrid coating material with polyurethane concentration of 5% and 10. The composition of ETP5% - Si 30% was the optimum composition from the ETP-Si hybrid coating material based on the mechanical analysis.Key words: hybrid coating, polyurethane, epoxy, silane, ETP – Si